Thariqah Tarjamah al-Nadzmi min al-Lughah al-‘Arabiyyah ila al-Manduriyah fi Kitabi Tuhfatul Athfal - Hamdy, Mohammad Zainal; Hadi, Abdul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
The translation of Arabic texts into Mandalorian is one of the difficulties that must be investigated through translation analysis, so the subject researcher chose the method of translating systems from Arabic into Mandalorian in the book Tuhfat al-Atfal. In this research, the researcher used the qualitative descriptive approach with the type of study, the library, and the research sources in this research, which are two types, the main source, which is the book Tuhfat al-Atfal, the Arabic and Mandurian system in the science of intonation. As for the research results obtained by the researcher in this research, the translation method used in the book Tuhfat al-Tilfa from Arabic into Manduriyah consists of two methods: the literal translation method and the freedom translation method.